STUDI PERBEDAAN ANTARA PRESTASI BELAJAR MANDIRI DENGAN BELAJAR PENDAMPINGAN MATA PELAJARAN PENDIDIKAN KEWARGANEGARAAN PADA SISWA TUNA WICARA SMALB - Retno Wati (Fakultas Keguruan dan Ilmu Pendidikan, 2016)
This study discusses the results of independent learning by assisting learning in PKB subjects specifically students of speech class XI SLALB SLB Negeri 2 Bantul. Total population of 7 students with census techniques, the population used as research. From the analysis results obtained t count of 13.28 while t table at a significance level of 5% of 2.26. With t arithmetic> t table there is a difference in independent learning achievement with Mentoring learning. Thus the hypothesis